Exploring sustainable purchasing and supply chain management through an institutional change lens: a systematic literature review - Chikwana, Josephine; Alinaghian, Leila; Razmdoost, Kamran (International Purchasing and Supply Education and Research Association (IPSERA), 2025)
The notion of sustainability within purchasing and supply chain management (PSCM) is not a recent development, as it has been evolving over the past few decades (Hoejmose & AdrienKirby, 2012; Johnsen et al., 2017; Miemczyk et al., 2012). Early discussions in PSCM focused primarily on environmental concerns, such as reducing carbon emissions, minimising waste, and improving energy efficiency within supply chains (Carter & Liane Easton, 2011; Seuring & Müller, 2008). Over time, the scope of sustainability expanded to include social and ethical dimensions, such as ensuring fair labour practices, promoting diversity and inclusion, and supporting local communities through procurement decisions (Yawar & Seuring, 2017; Zorzini et al., 2015).